Perfil cardiorrespiratório de pacientes com Osteoartrite de Joelho: estudo caso- controle - Nazario, Ana Karoline (Universidade Federal de São Carlos, 2025)
Knee osteoarthritis (KOA) is a chronic degenerative disease that affects functionality and quality of life, representing one of the leading causes of disability worldwide. Although aerobic exercise is widely recommended, there are still disagreements regarding its prescription, possibly due to a limited understanding of the cardiorespiratory profile of this population. Therefore, this study aimed to characterize the cardiorespiratory profile of individuals with KOA and to compare their functional performance and physical activity levels with individuals without the disease. Methods: Case-control study conducted according to STROBE guidelines. Participants included individuals with and without KOA (aged 40–65 years), who underwent a cardiopulmonary exercise test (CPET) and functional tests, including the 6-minute walk test (6MWT), 30-second sit-to-stand test (STS), timed up and go (TUG), stair climb test (SCT), and 40-meter walk test (40MWT). Cardiorespiratory variables were analyzed before, during, and after the tests. Statistical analyses were performed using SigmaPlot 11.0 software, with a significance level of p ≤ 0.05. Results: The study included 32 individuals with KOA and 27 controls. The KOA group showed lower aerobic functional capacity (V̇O2PEAK: 22.80 vs. 28.30 ml/kg/min, p ≤ 0.001), poorer performance in functional tests (6MWT: 444.19 vs. 593.74 m, p ≤ 0.001; TUG: 9.74 vs. 7.53 s, p ≤ 0.001), and hemodynamic alterations in response to exercise, with increased blood pressure and impaired heart rate recovery. They also exhibited lower levels of physical activity. Conclusion: Individuals with KOA demonstrated reduced aerobic and physical functional capacity, as well as altered hemodynamic responses to exercise. These findings highlight the importance of an integrated assessment for designing personalized exercise programs aimed at improving functionality and quality of life in this population.
Cardiorespiratory profile of patients with knee osteoarthritis: case-control study
Keywords: Osteoartrite de joelho; Capacidade cardiorrespiratória; Testes funcionais; Atividade física; Reabilitação; Knee osteoarthritis; Cardiorespiratory capacity; Functional tests; Physical activity; Rehabilitation; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL